Retracted: SLCO4A1‐AS1 promotes cell growth and induces resistance in lung adenocarcinoma by modulating miR‐4701‐5p/NFE2L1 axis to activate WNT pathway. (6th August 2020) - Wei, Yuxuan; Wei, Li; Li, Jiwei; Ma, Zeheng; Zhang, Quan; Han, Zhijun; Li, Saisai
Abstract: Long noncoding RNAs (lncRNAs) possessed essential functions in the biological behaviors of various human cancers. SLCO4A1 antisense RNA 1 (SLCO4A1‐AS1) is a lncRNA that has been reported as a oncogenic regulator in colorectal cancer and bladder cancer. However, whether it exerted functions in the gene expression and cellular processes in lung adenocarcinoma (LUAD) remains still obscure. In the present research, we unveiled the high level of SLCO4A1‐AS1 in LUAD tissues and cells. Moreover, functional assays indicated that SLCO4A‐AS1 facilitated LUAD cell proliferation, motility, and cisplatin‐resistance. Besides, mechanism investigation revealed that miR‐4701‐5p could interact with SLCO4A1‐AS1 and directly target to NFE2L1. The expression correlation between miR‐4701‐5p and SLCO4A1‐AS1 or NFE2L1 was found to be negative. Moreover, NFE2L1 was expressed at a same tendency with SLCO4A1‐AS1 in LUAD tissues and cells. In addition, it was confirmed that NFE2L1 was involved in SLCO4A1‐AS1‐mediated activation of WNT pathway. According to rescue assays, NFE2L1 could involve in SLCO4A1‐AS1‐mediated LUAD cell growth. Conclusively, our study demonstrated that SLCO4A1‐AS1 facilitated cell growth and enhanced the resistance of LUAD cells to chemotherapy via activating WNT pathway through miR‐4701‐5p/NFE2L1 axis. Abstract : Down‐regulation of SLCO4A1‐AS1 inhibits LUAD cell growth and promotes chemosensitivity. Up‐regulated SLCO4A1‐AS1 promotes LUAD cell growth and inhibits chemosensitivity. SLCO4A1‐AS1 acts as miR‐4701‐5p sponge in LUAD cells..